2015
DOI: 10.1111/andr.12141
|View full text |Cite
|
Sign up to set email alerts
|

No increased risk of coronary heart disease for patients receiving androgen deprivation therapy for prostate cancer in Chinese/Taiwanese men

Abstract: SUMMARYThe relationship between androgen deprivation therapy (ADT) and coronary heart disease (CHD) remains controversial. Furthermore, the majority of such studies focused on Caucasian populations, and there is still a paucity of studies among Asian populations. This population-based study aimed to investigate the relationship between ADT and CHD in an ethnic Chinese (i.e., Taiwanese) population. We used data sourced from the Taiwan 'Longitudinal Health Insurance Database'. This study included 1278 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…The final study sample consisted of 1714 PC patients, 868 patients who received ADT, the study group, and 846 patients who did not receive ADT, the comparison group. These selection criteria are consistent with prior studies [16]. …”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…The final study sample consisted of 1714 PC patients, 868 patients who received ADT, the study group, and 846 patients who did not receive ADT, the comparison group. These selection criteria are consistent with prior studies [16]. …”
Section: Methodssupporting
confidence: 77%
“…This dataset is available to academic researchers in Taiwan to extract samples as needed. As illustrated by several publications [1618], hundreds of studies using this dataset have been published in international peer-reviewed journals.…”
Section: Methodsmentioning
confidence: 99%
“…Our results are in agreement with previous Asian population-based studies, including the Japanese population [25] and the Taiwanese population [26]. The Japanese population study showed no increased risk of coronary heart disease in patients exposed to ADT.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Wang et al reported that coronary heart disease could be treated through modulating adrenergic, angiotensin, calcitonin, and neurotensin receptors of the neuroactive ligand-receptor interaction pathway [55] . In a 3-year, follow-up study, Wang et al [56] found that the recurrence rate of coronary heart disease was higher in patients with both coronary heart disease and prostate cancer than that in patients with coronary heart disease alone, suggesting that the incidence of coronary heart disease was closely linked to prostate cancer. Moreover, there is evidence to suggest that factor H and complement C3, of the complement and coagulation cascades pathway, are associated with heart disease [57,58] .…”
Section: Similarities and Differences In The Mechanisms Of Action Of mentioning
confidence: 99%